PENENTUAN KADAR RBB PADA SENYAWA INULIN-RBB SECARA HPLC - Minda Azhar; Budhi Oktavia; Yustini Ma’a; Khairani -; Devita Efri (Universitas Andalas, 2011)
ABSTRACT Inulin-RBB is a compound that used for screening of inulinase bacteria. Formation of inulin-RBB compounds in the mass variation of inulin and the reaction temperature and the determination of RBB concentation in inulin-RBB has been carried out. Determination of RBB concentration in inulin-RBB on the HPLC using an ODS C18 column, l 592 nm, mobile phase ethanol-water (60:40) and flow rate 1 mL/min. RBB concentration of inulin-RBB in the mass variation of inulin (2 g, 4 g and 6 g) which was reacted with 0.5 g of RBB at 50°C is 4.74%, 23.14%, and 38.54%, respectively. RBB concentration of inulin-RBB in the reaction with 0.5 g of inulin 4 g of RBB at the reaction temperature variations (40, 50 and 60 ° C) is 18.86%, 23.14%, 9.40%, respectively. Key words: RBB, inulin-RBB, inulin, HPLC